The last comics on earth. 1, A new dawn for the last kids on earth begins - Brallier, Max; Pruett, Joshua (The last comics on earth, 2023)
When friends Jack, Quint, June, and Dirk realize they read every issue of their favorite comic, Z-Man, the friends decide to write and illustrate their own comic book.